Mechanical thrombectomy in acute embolic stroke: preliminary results with the revive device - Rohde, Stefan; Hähnel, Stefan; Herweh, Christian; Pham, Mirko; Stampfl, Sibylle; Ringleb, Peter A.; Bendszus, Martin (Stroke, 2011)
Background and Purpose: The purpose of this study was to evaluate the safety and technical feasibility of a new thrombectomy device (Revive; Micrus Endovascular) in the endovascular treatment of acute ischemic stroke. Methods: Ten patients with acute large vessel occlusions were treated with the Revive device between October 2010 and December 2010. Mean National Institutes of Health Stroke Scale on admission was 19.0; mean duration of symptoms was 172 minutes. Recanalization was assessed using the Thrombolysis In Cerebral Infarction score. Clinical outcome (National Institutes of Health Stroke Scale) after thrombectomy was determined on Day 1, at discharge, and at Day 30. Results: Vessel recanalization (Thrombolysis In Cerebral Infarction 2b or 3) was successful in all patients without device-related complications. Mean National Institutes of Health Stroke Scale 24 hours after the intervention, at discharge, and at Day 30 was 14.0, 11.5, and 5.1, respectively. At Day 30, 6 patients had a clinical improvement of >8 points or an National Institutes of Health Stroke Scale of 0 to 1, 1 patient showed minor improvement, and 3 patients had died. Symptomatic intracranial hemorrhage occurred in 2 patients, of which 1 was fatal. Conclusions: Thrombectomy with the Revive device in patients with stroke with acute large vessel occlusions demonstrated to be technically safe and highly effective. Clinical safety and efficacy have to be established in larger clinical trials.
Gesehen am 19.09.2022